Semangat Berpasukan Berkualiti di Kalangan Pegawai-Pegawai Perkhidmatan Pendidikan di Negeri Perak - Gurcharan Singh, Bishen Singh (1997)
This study proposed to examine the level of quality teamwork among education service officers in the state of Perak. Quality teamwork is an element of Total Quality Management (TQM). Quality teamwork is studied along its elements - trust, communication, collaboration, leadership support, conflict handling, freedom of expression, and commitment of teams and their members in the surveyed institutions. Education service officers in this study referred to teachers and lecturers, including heads of unit, heads of department, senior assistants, vice principals and principals. The questionnaire in this study contained 29 items formulated by the researcher, 9 of which are on the personal characteristics of the respondents while another 20 based on the Likert scale of 1 to 5. The respondents of this study comprise of 458 education service officers from 3 teacher training colleges, 3 fully boarding secondary schools, 6 grade A secondary schools, 3 grade B secondary schools, 3 Chinese secondary schools and 4 Vocational Schools. Statistical tools used in this study were realibility test Cronbach Alpha), descriptive statistics test and analysis of variance (ANOVA). The level of confidence was set at 95% while degree of significance was determined at <O.05. Result of the data analysed showed that the overall mean value of quality teamwork was 3.59, which indicated a moderately high level. Element collaboration showed the highest mean of 3.96 whilst element communication showed the lowest mean at 3.14. t-test was applied to examine the difference in perceptions of male and female respondents on elements of quality teamwork. The data derived showed significant difference on elements trust, collaboration, and freedom of expression. T-test to examine the difference in perceptions of married and unmarried respondents showed significance on elements trust, collaboration, conflict handling, freedom of expressions, and commitment. T-test was also applied test the difference between respondents who have attended TQM related courses and respondents who have not had any such training. Significant difference was noted on elements collaboration, freedom of expression, and commitment. Analysis of variance (ANOVA) and Bonferroni test was also done in this study. ANOVA on respondents of different posts revealed significance difference level on elements trust, collaboration, leadership support, freedom of expression, and commitment. ANOVA on respondents of different age group, different institutions, different length of service, and different academic qualification did not show any significant difference. At the end of this study, discussion and recomendations are laid out to inculcate and enhance quality teamwork among education service officers.